Improving the speaking ability in English: The students’ perspective - Azizova Bakhora Numonovna; Sadikova Suriya Saidovna (Genius Journals, 2022)
This article is about improving the ability of speaking in English and the students’ perspective on it. There are several different kinds of methods which can be fruitful in developing students’ oral skills. Most essential methods are discussed in this article.
Keywords: Speaking; Oral Skills; Methods; Perspective